ASPIRASI RAKYAT DAN REFORMASI PARLEMEN - Yusuf, Al Muzzammil (Jurnal Penelitian Politik, 2025)
Survey shows that Indonesian citizens are not satisfied with the performance of their Parliament because the Members ofParliament do not do their function optimally in legislating controlling and budgeting It creates a democratic deficit Therefore a parliamentary reformation based on aspiration and participation of Indone sian citizens is very much needed The Reformation will be done through Policy Products Some ofthosepolicy products are including issuing Law that pro citizen strengthening public participation in controlling process of the Executive Board and using Media optimally as tools for political socialization and communication towards Indonesian citizens